2023
DOI: 10.4038/sljer.v10i2.182
|View full text |Cite
|
Sign up to set email alerts
|

A Flourishing or Faltering Economy: Unemployment Impacting Sri Lankan Economic Growth

Abstract: The primary goal of any economy is to achieve long-term economic growth while maintaining a stable rate of unemployment, which is a macroeconomic factor. Moreover, when unemployment rises, real Gross Domestic Product (GDP) falls short of potential GDP. Accordingly, the purpose of this study is to examine the impact of unemployment on the economic growth of Sri Lanka. By using data from the first quarter (Q1) of 2000 to the fourth quarter (Q4) of 2021 and Vector Error Correction Model (VECM) and Granger Causali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The stationarity of all variables has been established, as confirmed by the findings in Fig 3 . The VAR model is deemed stable when all the eigenvalues of its coefficient matrix are below one, as per the formal definition [ 20 , 46 , 48 ]. The S7 and S8 Appendices revealed that the eigenvalues in the researchers’ predictors fall within the unit circle; in Fig 3 , VAR model stratifies the stability criterion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stationarity of all variables has been established, as confirmed by the findings in Fig 3 . The VAR model is deemed stable when all the eigenvalues of its coefficient matrix are below one, as per the formal definition [ 20 , 46 , 48 ]. The S7 and S8 Appendices revealed that the eigenvalues in the researchers’ predictors fall within the unit circle; in Fig 3 , VAR model stratifies the stability criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Redlin [3], Gunarathne and Jayasinghe [10], Bonifazi, Heins [18], Atigala, Maduwanthi [20], Gardiyawasam, Ganegoda [21] HEÀ !Migration…”
Section: Variablementioning
confidence: 99%
See 2 more Smart Citations